Analisis Pemahaman Pelajar Tentang Peran Pancasila Sebagai Dasar Negara - Azzahra, Nazwa; Isnaini, Putri; Sabrina Nur Karimah Nst; Rumahombar, Cintya Agata; Jaya Damanik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine the level of mastery and application of Pancasila values as the state's philosophical foundation (Philosofische Grondslag) among Indonesian students, particularly in facing the currents of globalization and information disruption in the digital era. From a legal perspective, Pancasila holds the position of the state's fundamental norm (Staatsfundamentalnorm) which serves as the basis for the entire Indonesian legal system (Grundnorm), while also functioning as the nation's unifying bond and national worldview (Weltanschauung). The research employed a quantitative descriptive method with an incidental sampling technique involving 10 students as respondents. The data collection tool was a closed questionnaire using a Likert scale with four response options, evaluating four dimensions: (1) mastery of the five Sila principles, (2) understanding of Pancasila as the state foundation, (3) historical knowledge of the Pancasila formulation, and (4) practice of Pancasila values in daily activities. The findings indicate a very adequate level of understanding among respondents regarding Pancasila's position as the state foundation (93.3% Strongly Agree) and the urgency of understanding Pancasila for all Indonesian people (93.3% Strongly Agree). The majority of respondents felt capable of describing the five Sila principles (73.3% Strongly Agree) and understood Pancasila's function in maintaining national unity. The implementation of Pancasila values in daily behavior, such as tolerant attitudes and the spirit of gotong royong (mutual cooperation), showed a high level of affirmation (an accumulation of 86.6% Agree and Strongly Agree). Nevertheless, a gap in understanding was identified in the dimension of the history of Pancasila's formulation, with 20% of respondents giving a neutral response. Educational institutions were deemed to have contributed effectively (a total of 93.3% Agree and Strongly Agree) in promoting the internalization of these values.Comprehensively, the level of student understanding of Pancasila as the state foundation is categorized as satisfactory. This study suggests strengthening the learning material regarding the historical process of Pancasila's ratification and innovation in teaching methods that are more contextual, creative, and applicable (educational, recreational, reflective, and futuristic) to ensure the comprehensive internalization of Pancasila values—covering cognitive, affective, and psychomotor aspects—as a pillar of national ideological resilience in facing future challenges.